2018
DOI: 10.1111/jam.13761
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flask configuration on biofilm growth and metabolites of intertidal Cyanobacteria isolated from a mangrove forest

Abstract: The present study augmented the information which can enhance wider exploration of the biofilm mode of cultivation of Cyanobacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 78 publications
0
7
1
Order By: Relevance
“…While it is accepted that the true ecological role of many microbial SMs has not been experimentally validated, antibiotic production has long been believed to be involved in competitive inhibition of the growth of proximal microbes or possibly in intercellular signaling. The Mukherjee group reported several findings connecting vessel types, lifestyles, and SM production in various microorganisms [ 79 , 80 , 81 ]. For example, Mitra and colleagues designed a conico-cylindrical flask (CCF) with an ultra-low-speed rotating disk bioreactor [ 79 ].…”
Section: Change In Physical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is accepted that the true ecological role of many microbial SMs has not been experimentally validated, antibiotic production has long been believed to be involved in competitive inhibition of the growth of proximal microbes or possibly in intercellular signaling. The Mukherjee group reported several findings connecting vessel types, lifestyles, and SM production in various microorganisms [ 79 , 80 , 81 ]. For example, Mitra and colleagues designed a conico-cylindrical flask (CCF) with an ultra-low-speed rotating disk bioreactor [ 79 ].…”
Section: Change In Physical Parametersmentioning
confidence: 99%
“…AP3b, and Chroococcus sp. AP3U [ 81 ]. Upon comparing the metabolite profiles of these strains, grown in biofilms in the CCF-PMMA, to those of the same strains grown as plankton in a standard EF; they found that biofilms formed in the CCF but not in the EF and that cell-bound polysaccharide and released polysaccharide production was higher in CCF than in EF.…”
Section: Change In Physical Parametersmentioning
confidence: 99%
“…Benthic biofilms are highly adapted to changing environmental conditions (dramatic changes in environmental parameters and nutrient concentrations) and are absorbers of excess nutrients from the environment [ 77 ]. The trichomes of the Baikal strain tightly intertwine and form a biofilm, characteristic of many species of Oscillatoriales cyanobacteria, in which the bacteria are held together by a polysaccharide mucus that is able to withstand harsh environmental conditions that might involve nutrient deficiencies and physical stress [ 78 ]. Various types of microscopy have been used to study the morphology of biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, increased levels of capsular/ bound polysaccharides were observed when fermentation of Leptolyngbya sp. was carried out in biofilm culture in conicocylindrical flasks compared to culture in planktonic mode in Erlenmeyer flasks (Veerabadhran et al 2018). Metabolomics can also be used to analyze the behavior of cyanobacterial strains subjected to stress conditions.…”
Section: Introductionmentioning
confidence: 99%